Effectiveness of Mediation in Alternative Dispute Settlement in the Implementation of Systematic Land Registration (PTSL) - Sugiyono Sugiyono; Diyan Isnaeni; Abdul Rolhim (Budapest International Research and Critics University, 2022)
Land is an important part of life in society. The occurrence of land problems that exist in the community is usually only done by litigation in handling the dispute process. This study aims to identify and analyze the development of land rights law. The development of the science of land rights law is related to the effectiveness of mediation in resolving land rights disputes to obtain a comprehensive picture of alternative dispute resolution. This type of research is a juridical-empirical research. Empirical juridical research is research on secondary data in the form of applicable legal aspects, then proceeds to primary data research in the form of research on real phenomena that occur in the field. The results of this study show that several cases related to land disputes have been successfully resolved by alternative land dispute resolution outside the trial, especially with mediation. Based on the research that has been done, it can be concluded that the effectiveness of mediation in alternative settlement of complete systematic land registration disputes (PTSL) in the village of Pengkoljagong, Jati District, Blora Regency, is very effective.